The Reality and Prospects of Pneumococcal Vaccination during the COVID-19 Pandemic - E. A. Orlova; I. P. Dorfman; O. V. Shatalova; M. A. Orlov; R. M. Mamina; N. N. Mochalova (Эпидемиология и вакцинопрофилактика, 2022)
Relevance. Pneumococcal infection (PI) is one of the leading causes of disability and death of older people worldwide. In the Astrakhan region, as in other regions of the Russian Federation, there is a low coverage of pneumococcal vaccination (PV) and amounts to 1.3% of the adult population. This study reflects the regional problem of PV, an evaluation of its effectiveness in reducing exacerbations and the development of community-acquired pneumonia (CAP) in patients with COPD. The impact of pneumococcal infection (PI) in the development of pneumonia turned out in the period of the COVID-19 pandemic so far to be the most significant.Aim of this work was to evaluate the level of doctor’s awareness in the issues of pneumococcal vaccination, as well as the results of its implementation in patients with COPD during COVID-19 pandemic.Materials and methods. The study was conducted in the form of a survey in the period from October 2021 to February 2022. A survey was conducted through a questionnaire poll in polyclinics and pulmonology departments of multidisciplinary hospitals in Astrakhan. A total of 201 doctors and 173 patients suffering from COPD participated in the study. The doctors' responses were compared with the results of the survey conducted in 2018.Results. This study shows that 26% of the surveyed patients with COPD were vaccinated with pneumococcal vaccine. Analysis of clinical effects after vaccination shows that exacerbations of COPD were absent during the year in 51.1% of vaccinated patients, and 35.2% in non-vaccinated group. The prevalence of CAP in vaccinated patients was 13.3% vs 32.4% in patients who did not receive vaccination.Conclusion. This study showed a significant level of clinical efficacy of PV, characterized by a reduced incidence of COPD exacerbations and the development of VP in vaccinated patients, as well as a lower number of hospitalizations. Vaccinated patients reported mild severity of coronavirus infection, which determines the high prospects for further PV research as one of the important measures to counteract the COVID-19 pandemic. The problem of awareness in specialists about pneumococcal vaccination requires further improvement of educational programs on the relevant topic in the framework of continuing medical education.